Low-porosity high-cycle solid-state pole piece, battery and energy storage equipment
By using a polymerizable composite electrolyte in the battery electrode sheet, including a cyclic lactone-based ionic liquid and a reactive reactive group polymer monomer, the problem of high porosity and reaction of PVDF adhesive in the traditional battery electrode sheet is solved, and a battery electrode sheet with low porosity and high circulation performance is achieved.
Patent Information
- Application Number
- CN202411945334.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The high porosity of traditional battery poles leads to waste of energy density, and the polyvinylidene fluoride (PVDF) adhesive used may react with lithium metal during the battery operation, affecting circulation performance and safety.
The polymerizable composite electrolyte is used, including cyclic lactone-based ionic liquid, reactive group polymer monomer and electrolyte nanoparticles, and the electrode sheet performance is optimized through the combination effect and replaced traditional PVDF as the adhesive.
It effectively reduces the porosity of the pole plate, improves the cycle performance and safety performance of the battery, and improves the overall performance and service life of the battery.
Smart Images

Figure CN119786535A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a low-porosity, high-cycle solid-state electrode. Background Art
[0002] With the development of new energy industry, the market demand for battery capacity is getting higher and higher. However, it is difficult to meet people's demand for long battery life by simply improving and optimizing materials. People have to find other ways to further improve battery capacity density. Among them, because the traditional battery coating roller pressing process uses a large amount of solvent in wet coating, this will cause a large number of holes to form after coating and drying. Due to the limited force of substrate rolling, it is difficult to achieve high density after rolling, which undoubtedly limits the ability to improve battery capacity density. Therefore, one solution is to increase battery capacity density by reducing the porosity of the pole piece. However, this brings another problem. Low porosity may limit the conductivity of ions in the electrode and make it difficult to dissipate heat. In addition, polyvinylidene fluoride (PVDF) is usually used as an adhesive in traditional processes. It may react with lithium metal during battery operation, further releasing a large amount of heat, which seriously affects the battery's cycle performance and safety capabilities. At the same time, PVDF may also absorb electrolyte excessively, resulting in uneven distribution of electrolyte inside the battery, which further affects the battery's ionic conductivity and overall conductivity. Under the combined effect of low porosity and PVDF, although the battery capacity has been improved to a certain extent, its safety performance and cycle performance often deteriorate sharply. How to fully utilize the advantages brought by low porosity and avoid its impact on cycle and electrochemical performance has become a major difficulty in current research. Summary of the invention
[0003] In order to solve the problems of the prior art, the present invention provides a low-porosity and high-cycle solid-state electrode. By replacing the slurry solvent with a polymerizable composite electrolyte and utilizing the compounding effect between the cyclic lactone-based ionic liquid, polymer monomer and electrolyte nanoparticles in the polymerizable composite electrolyte, the electrode performance is optimized from three aspects: slurry preparation, electrode preparation and battery cycle. The problem of energy density waste caused by the high porosity of traditional electrodes is solved, and at the same time, the ionic conductivity and overall conductive performance of the electrode are improved, thereby obtaining a low-porosity, high-cycle performance electrode.
[0004] In a first aspect, the present invention further provides a low-porosity, high-cycle solid-state electrode, comprising a current collector and an active material layer disposed on the current collector and comprising a modified material: wherein the synthetic monomer of the modified material comprises a first type of monomer and a second type of monomer; the first type of monomer comprises a cyclic lactone-based ionic liquid having a structure of formula I, the second type of monomer comprises a polymer monomer having at least one reactive active group, the polymer monomer having a carbon-carbon unsaturated bond, and the electrode further comprises electrolyte nanoparticles;
[0005] The cyclic lactone-based ionic liquid having the structure of formula I is
[0006]
[0007] Wherein, X is an oxygen heterocyclic group, Y + is an ionic liquid cationic group;
[0008] R is one of a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted alkyl ester group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted cycloalkyl group, and when substituted, the substituent is selected from halogen;
[0009] Z - One or more selected from the group consisting of halogen ions, phosphate ions, perchlorate ions, sulfonimide ions, oxalate borate ions, sulfonate ions, and acetate ions;
[0010] The reactive active group is selected from any one of vinyl, allyl, epoxypropyl, amine and hydroxyl groups or a combination of two or more thereof.
[0011] As a further scheme, the oxygen heterocyclic group is selected from one of a cyclic carbonate group, a cyclic sulfate group, a sultone group, a cyclic phosphonate group, and a carboxylate group; the ionic liquid cationic group is selected from one of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrolidine, and piperidine functionalized ionic liquid cationic groups; the R is selected from one of a C1-C8 substituted or unsubstituted alkyl group, a C1-C8 substituted or unsubstituted alkoxy group, a C1-C8 substituted or unsubstituted alkyl ester group, a C2-C8 substituted or unsubstituted unsaturated hydrocarbon group, and a C3-C8 substituted or unsubstituted cyclic hydrocarbon group, and when substituted, the substituent is selected from a halogen.
[0012] As a further scheme, the oxygen heterocyclic group is selected from a cyclic carbonate group, the ionic liquid cationic group is selected from one of quaternary ammonium and imidazole ionic liquid cationic groups, and the R is selected from a C1-C6 substituted or unsubstituted alkyl ester group, and when substituted, the substituent is selected from a halogen.
[0013] As some exemplary schemes, the cyclic lactone-based ionic liquid having the structure of formula I is selected from
[0014]
[0015]
[0016] Any one or more of them.
[0017] As a further embodiment, the polymer monomer is selected from chain polymer monomers having an unsaturated carbon-carbon bond at the end.
[0018] As a further solution, the chain polymer monomer with unsaturated carbon-carbon bonds at the ends is selected from chain polymer monomers with unsaturated carbon-carbon bonds at both ends. Chain polymer monomers with unsaturated carbon-carbon bonds at both ends help to further optimize the cross-linking structure during the polymerization process, forming a more orderly and stable cross-linking network, thereby improving the bonding strength and the electrochemical ability of the electrode.
[0019] As a further solution, the electrolyte nanoparticles have a particle size of less than 500 nm.
[0020] As a further solution, the material of the electrolyte nanoparticles is selected from any one or more of inorganic ceramic electrolytes, inorganic salt electrolytes, phosphate electrolytes, and sulfate electrolytes.
[0021] As a further solution, the material of the electrolyte nanoparticles is selected from inorganic ceramic electrolytes.
[0022] As a further solution, the polymerizable composite electrolyte also includes a lithium salt.
[0023] As a further embodiment, the lithium salt is selected from lithium salts having a decomposition temperature higher than 80°C.
[0024] As a further solution, the active material layer also includes an initiator.
[0025] As a further solution, the initiator is selected from at least one of peroxides, azo compounds and persulfates.
[0026] As a further solution, the mass ratio of the cyclic lactone-based ionic liquid having a structure of formula I, the polymer monomer, the electrolyte nanoparticles, and the lithium salt in the polymerizable composite electrolyte is selected from the range of (50-95): (0.1-40): (0.1-20): (5-20).
[0027] As a further solution, the mass proportion of the cyclic lactone-based ionic liquid having the structure of formula I in the polymerizable composite electrolyte is selected from 55 to 85 wt %.
[0028] As a further solution, the mass proportion of the polymer monomer having at least one reactive active group in the polymerizable composite electrolyte is selected from 10 to 30 wt %.
[0029] As a further solution, the total mass ratio of the initiator to the cyclic lactone-based ionic liquid and the polymer monomer is (0.5-5):100.
[0030] As a further solution, the mass proportion of the polymerizable composite electrolyte in the coating slurry is 10 to 35 wt %.
[0031] As a further solution, the coating slurry of the low-porosity and high-cycle solid-state electrode also includes active material particles and conductive additives.
[0032] As a further solution, the type of active material particles is not limited in principle, and can be, for example, selected from any one of carbon-based materials, silicon-based materials, and metal oxides.
[0033] As a further solution, the type of the conductive additive is not limited in principle, and can be, for example, selected from any one or more of conductive carbon black, conductive polymers, graphite, graphene oxide, reduced graphene oxide, carbon nanotubes, conductive carbon fibers, activated carbon, porous carbon materials, copper powder, aluminum powder, conductive silicates, polyaniline, polypyrrole, polyvinyl pyrrolidone, nitrogen-doped carbon materials, and carbon microspheres.
[0034] As a further solution, the conductive additive accounts for 3 to 15 wt % in the coating slurry.
[0035] As a further solution, the mass proportion of the active material particles in the coating slurry is 60-85wt%.
[0036] As a further solution, the low-porosity and high-cycle solid-state electrode also includes a current collector.
[0037] As a further solution, the material of the current collector is not limited in principle, and can be, for example, selected from any one of aluminum foil, copper foil, nickel foil, and stainless steel.
[0038] As a further solution, the low-porosity high-cycle solid-state electrode has a porosity of 0.5-10%.
[0039] As a further solution, the low-porosity, high-cycle solid-state electrode may be any one of a positive electrode and a negative electrode.
[0040] As a further solution, the low-porosity, high-cycle solid-state electrode is preferably a positive electrode.
[0041] As a further solution, the low porosity high cycle solidification electrode surface loading is 17-25 mg / cm2 .
[0042] In a second aspect, the present invention provides a method for synthesizing a low-porosity, high-cycle solid-state electrode, comprising the following steps:
[0043] S1.1: Mix the first type of monomer, the second type of monomer, the electrolyte nanoparticles, and the lithium salt in a stoichiometric ratio to obtain a first solution;
[0044] S1.2: According to the stoichiometric ratio, the initiator is added to the first solution and mixed evenly to obtain the second solution, followed by coating, and then curing to obtain a low-porosity, high-cycle solid-state electrode;
[0045] Among them, the active material and the conductive agent are introduced into the low-porosity and high-cycle solid-state electrode by one of the following two methods.
[0046] Method 1: The active material and the conductive agent are arranged in the active material layer on the surface of the current collector, and the second solution prepared in step S1.2 is applied to the surface of the active material layer, and then solidified to obtain a low-porosity, high-cycle solid-state electrode.
[0047] Method 2: The active material and the conductive agent are added to the second solution in step S1.2, and then coated on the surface of the current collector, and then cured to obtain a low-porosity, high-cycle solid-state electrode.
[0048] As a further solution, the specific steps of method 1 are:
[0049] S2.1: Add the active material and the conductive agent to the solvent according to the stoichiometric ratio, mix them evenly and then apply them on the surface of the current collector to obtain a current collector provided with an active material layer;
[0050] S2.2: Mixing the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt uniformly according to the stoichiometric ratio to obtain a first solution;
[0051] S2.3: According to the stoichiometric ratio, the initiator is added to the first solution and mixed evenly to obtain a second solution, and the second solution is coated on the surface of the active material layer on the current collector. After thermal curing, a low-porosity and high-cycle solid-state electrode is obtained.
[0052] As a further solution, the specific steps of method 2 are:
[0053] S3.1: Mixing the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt uniformly according to the stoichiometric ratio to obtain a first solution;
[0054] S3.2: According to the stoichiometric ratio, the initiator, the active material and the conductive agent are added to the first solution to obtain a second solution, and the second solution is coated on the surface of the current collector. After thermal curing, a low-porosity and high-cycle solid-state electrode is obtained.
[0055] As a further solution, method 2 is a preferred synthesis method.
[0056] As a further solution, the thermal curing conditions are 70-90° C. in a vacuum environment and curing for 10-14 hours.
[0057] As a further solution, the solvent is not limited in principle, and technicians can select the corresponding solvent according to their needs.
[0058] As a further solution, the method for synthesizing the first type of monomer comprises the following steps:
[0059] S4.1: In a first solvent, heating a first reactant having a structural formula of XRM and an ionic liquid to reflux, cooling, washing, and distilling under reduced pressure to obtain a cyclic lactone-based ionic liquid, wherein X is an oxygen heterocyclic group and M is a halogen;
[0060] The ratio of the first reactant to the ionic liquid is 1:1.05-2, preferably 1:1.1-1.5.
[0061] S4.2: In a second solvent, stir and wash the cyclic lactone-based ionic liquid and the alkali metal salt to obtain the electrolyte additive.
[0062] The mass ratio of the cyclic lactone-based ionic liquid to the alkali metal salt is 1:1.05-2, preferably 1:1.1-1.5.
[0063] As a further solution, the first solvent in step S4.1 is ethyl acetate.
[0064] As a further solution, the ionic liquid in step S4.1 is selected from one of imidazoles, pyridines, quaternary ammoniums, quaternary phosphoniums, pyrrolidines, piperidines, and functionalized ionic liquids.
[0065] As some preferred schemes, the ionic liquid is selected from the group consisting of N-methylimidazole, triethylamine, 4-methylpyridine, 1-methylpyrrolidine, N-methylpiperidine, and N,N-diethylmethylamine.
[0066] As a further solution, the heating reflux temperature in step S4.1 is 60-90°C.
[0067] As a further solution, in step S4.2, the second solvent is deionized water.
[0068] As a further solution, in step S4.2, the alkali metal salt is selected from one or more of halide ions, phosphate ions, perchlorate ions, sulfonimide ions, oxalate borate ions, sulfonate ions, and acetate ions.
[0069] As a further solution, in step S4.2, the stirring time is 2 to 24 hours.
[0070] On the third aspect, the present solution also provides a battery that uses a low-porosity, high-cycle solid-state electrode as the electrode.
[0071] In a fourth aspect, the present solution also provides an energy storage device, including the battery.
[0072] Compared with the prior art, the present invention has at least the following beneficial effects:
[0073] This scheme proposes an innovative low-porosity, high-cycle solid-state electrode to improve battery capacity density and optimize battery cycle performance. This technology achieves the preparation of low-porosity electrodes by using a polymerizable composite electrolyte containing cyclic lactone-based ionic liquids, reactive active group polymer monomers and solid electrolyte nanoparticles. This composite electrolyte forms a cross-linked network during the curing process, replacing traditional PVDF as an adhesive while improving heat dissipation and ion conductivity. The introduction of inorganic ceramic electrolyte nanoparticles regulates the polymer cross-linking density, constructs ion transport channels, improves conductivity and ion migration number, and adsorbs impurities in the electrolyte, enhancing the safety performance of the battery. During the battery cycle, the cyclic lactone-based ionic liquid undergoes a ring-opening polymerization reaction to form a solid electrolyte membrane, which further improves ionic conductivity and inhibits side reactions. Combining these effects, this scheme effectively reduces the electrode porosity, optimizes electrochemical performance, improves battery cycle performance, and significantly improves the overall performance and service life of the battery. DETAILED DESCRIPTION
[0074] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.
[0075] In the first aspect, the present invention also provides a low-porosity, high-cycle solid-state electrode, comprising a current collector and an active material layer disposed on the current collector and comprising a modified material: wherein the synthetic monomer of the modified material comprises a first type of monomer and a second type of monomer; the first type of monomer comprises a cyclic lactone-based ionic liquid having a structure of formula I, the second type of monomer comprises a polymer monomer having at least one reactive active group, the polymer monomer having a carbon-carbon unsaturated bond, the electrode also comprises electrolyte nanoparticles, and the cyclic lactone-based ionic liquid having a structure of formula I is
[0076]
[0077] Wherein, X is an oxygen heterocyclic group, Y + is an ionic liquid cationic group;
[0078] R is one of a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted alkyl ester group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted cycloalkyl group, and when substituted, the substituent is selected from halogen;
[0079] Z - One or more selected from the group consisting of halogen ions, phosphate ions, perchlorate ions, sulfonimide ions, oxalate borate ions, sulfonate ions, and acetate ions;
[0080] The reactive active group is selected from any one of vinyl, allyl, epoxypropyl, amine and hydroxyl groups or a combination of two or more thereof.
[0081] In order to further improve the battery capacity density and optimize the battery cycle performance, this solution provides a low-porosity and high-cycle solid-state electrode. The cyclic lactone-based ionic liquid with a structure of Formula I, a polymer monomer with at least one reactive active group, and solid electrolyte nanoparticles in the polymerizable composite electrolyte can be compounded with each other during electrode curing and battery cycling, thereby reducing the electrode porosity while optimizing the ionic conductivity and improving the battery cycle capacity.
[0082] Specifically, in the polymerizable composite electrolyte of the low-porosity and high-cycle solid-state electrode, the cyclic lactone-based ionic liquid having a structure of Formula I and the polymer monomer having at least one reactive active group can firstly act as a solvent to uniformly disperse the active material particles and solutes such as the conductive agent in the slurry, thereby replacing the solvent in the traditional process and avoiding the problem of excessive porosity due to solvent volatilization, thereby obtaining a low-porosity electrode and increasing the surface loading of the electrode.
[0083] Subsequently, in the process of cross-linking and curing of polymer monomers having at least one reactive active group, the uniformly dispersed solutes and cyclic lactone-based ionic liquids are uniformly fixed in the cross-linked network. On the one hand, the cross-linked polymer monomer network can act as an adhesive to achieve the fixation of active material particles and solutes such as conductive agents, and can further improve the heat dissipation capacity of the battery; on the other hand, the cross-linked network helps to construct ion transmission channels, thereby improving the ion conductivity of the electrode; the high cross-linking strength of the polymer helps to ensure the effectiveness of the bonding, but too high a cross-linking density may have a counter-effect on the ion conductivity, therefore, we further introduced electrolyte nanoparticles into the polymerizable composite electrolyte raw material; the introduction of electrolyte nanoparticles, on the one hand, helps to adjust the polymer cross-linking density while ensuring the bonding strength, on the other hand, can also cooperate with the polymer cross-linking network to construct ion transmission channels, thereby improving the conductivity and ion migration number, in addition, the introduction of electrolyte nanoparticles can also adsorb trace impurities (such as water) in the electrolyte, thereby improving the battery's safety and performance cycle capability.
[0084] During the cycle, the cyclic lactone in the cyclic lactone-based ionic liquid uniformly coated on the solute undergoes a ring-opening polymerization reaction, forming a dense solid electrolyte membrane around the active material particles and the conductive agent particles, thereby further improving the ionic conductivity and inhibiting the side reaction between the active material particles and the electrolyte. Under the joint action of the cyclic lactone-based ionic liquid, polymer and solid electrolyte nanoparticles having the structure of Formula I, the polymerizable composite electrolyte provided by the present invention can effectively reduce the porosity of the electrode, while optimizing the electrochemical capacity of the electrode and improving the battery cycle performance.
[0085] As a further scheme, the oxygen heterocyclic group is selected from one of a cyclic carbonate group, a cyclic sulfate group, a sultone group, a cyclic phosphonate group, and a carboxylate group; the ionic liquid cationic group is selected from one of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrolidine, and piperidine functionalized ionic liquid cationic groups; the R is selected from one of a C1-C8 substituted or unsubstituted alkyl group, a C1-C8 substituted or unsubstituted alkoxy group, a C1-C8 substituted or unsubstituted alkyl ester group, a C2-C8 substituted or unsubstituted unsaturated hydrocarbon group, and a C3-C8 substituted or unsubstituted cyclic hydrocarbon group, and when substituted, the substituent is selected from a halogen.
[0086] As a further scheme, the oxygen heterocyclic group is selected from a cyclic carbonate group, the ionic liquid cationic group is selected from one of the quaternary ammonium and imidazole ionic liquid cationic groups, and the R is selected from a substituted or unsubstituted alkyl ester group of C1 to C6, and the substituent is selected from a halogen when substituted. We believe that compared with other ionic liquid cationic groups, quaternary ammonium and imidazole ionic liquid cationic groups can better achieve solute dispersion in combination with polymer monomers, thereby constructing a more uniform cross-linked network. At the same time, during the cycle process, quaternary ammonium and imidazole help to form a more stable CEI membrane, thereby optimizing the cycle performance and electrochemical ability of the electrode. In addition, the oxygen heterocyclic group selected from the cyclic carbonate group helps to further enhance the ionic conductivity of the electrolyte and form a more uniform cross-linked network during the polymerization cross-linking process. Finally, since the substituted or unsubstituted alkyl ester group of C1 to C6 usually has good solubility and helps to form a more uniform slurry, it is preferred that R is a substituted or unsubstituted alkyl ester group of C1 to C6, and the substituent is selected from a halogen when substituted.
[0087] As some exemplary schemes, the cyclic lactone-based ionic liquid having the structure of formula I is selected from
[0088]
[0089] Any one or more of them.
[0090] As a further solution, the polymer monomer is selected from a chain polymer monomer having an unsaturated carbon-carbon bond at the end. The chain polymer monomer having an unsaturated carbon-carbon bond at the end helps to further optimize the cross-linked network structure, construct a higher content of lithium ion channels, and thus optimize the electrochemical capacity of the electrode.
[0091] As a further solution, the chain polymer monomer having an unsaturated carbon-carbon bond at the end is selected from a chain polymer monomer having unsaturated carbon-carbon bonds at both ends. The chain polymer monomer having unsaturated carbon-carbon bonds at both ends helps to further optimize the cross-linking structure during the polymerization process, forming a more ordered and stable cross-linking network, thereby improving the bonding strength and electrochemical capability of the electrode.
[0092] As a further solution, the electrolyte nanoparticles have a particle size of less than 500 nm.
[0093] As a further solution, the material of the electrolyte nanoparticles is selected from any one or more of inorganic ceramic electrolytes, inorganic salt electrolytes, phosphate electrolytes, and sulfate electrolytes.
[0094] As a further solution, the electrolyte nanoparticle material is preferably an inorganic ceramic electrolyte, and the inorganic ceramic electrolyte is selected from aluminum fluoride, lithium oxide, aluminum oxide, lithium sulfide, sodium oxide, calcium oxide, zirconium oxide, lithium phosphate, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 , TiO2, AlO2, SiO2, any one or more.
[0095] As a further solution, the polymerizable composite electrolyte further includes lithium salt. The addition of lithium salt helps to further promote the construction of ion channels and improve the electrochemical performance of the battery.
[0096] As a further embodiment, the lithium salt is selected from lithium salts having a decomposition temperature higher than 80°C.
[0097] As a further embodiment, the lithium salt is selected from one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, and lithium hexafluorophosphate.
[0098] As a further solution, the active material layer also includes an initiator.
[0099] As a further solution, the initiator is selected from at least one of peroxides, azo compounds and persulfates.
[0100] As a further embodiment, the peroxide is selected from at least one of dibenzoyl peroxide, dialkyl peroxide, tert-butyl hydroperoxide, and isopropylbenzene hydroperoxide.
[0101] As a further embodiment, the azo compound is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azodiphenylnitrile and disodium azodiacetate.
[0102] As a further embodiment, the persulfate is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, and calcium persulfate.
[0103] As a further solution, the mass ratio of the cyclic lactone-based ionic liquid having a structure of formula I, the polymer monomer, the electrolyte nanoparticles, and the lithium salt in the polymerizable composite electrolyte is selected from the range of (50-95): (0.1-40): (0.1-20): (5-20).
[0104] As a further solution, the mass proportion of the cyclic lactone-based ionic liquid having the structure of formula I in the polymerizable composite electrolyte is selected from 55 to 85 wt %.
[0105] As a further solution, the mass proportion of the polymer monomer having at least one reactive active group in the polymerizable composite electrolyte is selected from 10 to 30 wt %.
[0106] As a further solution, the total mass ratio of the initiator to the cyclic lactone-based ionic liquid and the polymer monomer is (0.5-5):100.
[0107] As a further solution, the mass proportion of the polymerizable composite electrolyte in the coating slurry is 10 to 35 wt %.
[0108] As a further solution, the coating slurry of the low-porosity and high-cycle solid-state electrode also includes active material particles and conductive additives.
[0109] As a further solution, the type of active material particles is not limited in principle, and can be, for example, selected from any one of carbon-based materials, silicon-based materials, and metal oxides.
[0110] As a further solution, the carbon-based material is selected from any one of graphite, graphene oxide, reduced graphene oxide, carbon nanotubes, carbon fiber, activated carbon, carbon black, foamed carbon, carbon microspheres, and porous carbon materials.
[0111] As a further solution, the silicon-based material is selected from any one of silicon, silicon oxide, silicon-carbon composite material, and porous silicon.
[0112] As a further solution, the metal oxide is selected from any one of cobalt oxide, manganese oxide, nickel oxide, iron oxide, sodium tungstate, zinc oxide, and composite metal oxide.
[0113] As a further embodiment, the composite metal oxide is selected from NCM811, lithium cobalt oxide, lithium manganese oxide, nickel manganese oxide, lithium iron phosphate, LiMn 1.5 Ni 0.5 Any one of O4.
[0114] As a further solution, the type of the conductive additive is not limited in principle, and can be, for example, selected from any one or more of conductive carbon black, conductive polymers, graphite, graphene oxide, reduced graphene oxide, carbon nanotubes, conductive carbon fibers, activated carbon, porous carbon materials, copper powder, aluminum powder, conductive silicates, polyaniline, polypyrrole, polyvinyl pyrrolidone, nitrogen-doped carbon materials, and carbon microspheres.
[0115] As a further solution, the conductive additive accounts for 3 to 15 wt % in the coating slurry.
[0116] As a further solution, the mass proportion of the active material particles in the coating slurry is 60-85wt%.
[0117] As a further solution, the low porosity high cycle solidification electrode surface loading is 17-25 mg / cm 2 .
[0118] As a further solution, the low-porosity and high-cycle solid-state electrode also includes a current collector.
[0119] As a further solution, the material of the current collector is not limited in principle, and can be, for example, selected from any one of aluminum foil, copper foil, nickel foil, and stainless steel.
[0120] As a further solution, the low-porosity high-cycle solid-state electrode has a porosity of 0.5-10%.
[0121] As a further solution, the low-porosity, high-cycle solid-state electrode may be any one of a positive electrode and a negative electrode.
[0122] As a further solution, the low-porosity and high-cycle solid-state electrode is preferably a positive electrode. When the prepared low-porosity and high-cycle solid-state electrode is a positive electrode, the presence of the second type of monomer helps to replace PVDF as a binder to achieve the fixation of positive electrode active material particles and solutes such as conductive agents.
[0123] In a second aspect, the present invention provides a method for synthesizing a low-porosity, high-cycle solid-state electrode, comprising the following steps:
[0124] S1.1: Mix the first type of monomer, the second type of monomer, the electrolyte nanoparticles, and the lithium salt in a stoichiometric ratio to obtain a first solution;
[0125] S1.2: According to the stoichiometric ratio, the initiator is added to the first solution and mixed evenly to obtain the second solution, followed by coating, and then curing to obtain a low-porosity, high-cycle solid-state electrode;
[0126] Among them, the active material and the conductive agent are introduced into the low-porosity and high-cycle solid-state electrode by one of the following two methods.
[0127] Method 1: The active material and the conductive agent are arranged in the active material layer on the surface of the current collector, and the second solution prepared in step S1.2 is applied to the surface of the active material layer, and then solidified to obtain a low-porosity, high-cycle solid-state electrode.
[0128] Method 2: The active material and the conductive agent are added to the second solution in step S1.2, and then coated on the surface of the current collector, and then cured to obtain a low-porosity, high-cycle solid-state electrode.
[0129] As a further solution, the specific steps of method 1 are:
[0130] S2.1: Add the active material and the conductive agent to the solvent according to the stoichiometric ratio, mix them evenly and then apply them on the surface of the current collector to obtain a current collector provided with an active material layer;
[0131] S2.2: Mixing the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt uniformly according to the stoichiometric ratio to obtain a first solution;
[0132] S2.3: According to the stoichiometric ratio, the initiator is added to the first solution and mixed evenly to obtain a second solution, and the second solution is coated on the surface of the active material layer on the current collector. After thermal curing, a low-porosity and high-cycle solid-state electrode is obtained.
[0133] As a further solution, the specific steps of method 2 are:
[0134] S3.1: Mixing the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt uniformly according to the stoichiometric ratio to obtain a first solution;
[0135] S3.2: According to the stoichiometric ratio, the initiator, the active material and the conductive agent are added to the first solution to obtain a second solution, and the second solution is coated on the surface of the current collector. After thermal curing, a low-porosity and high-cycle solid-state electrode is obtained.
[0136] The two low-porosity, high-cycle solid-state electrode preparation methods provided in this scheme can both obtain low-porosity, high-cycle solid-state electrode with low porosity. When method 1 is used to prepare the low-porosity, high-cycle solid-state electrode, the presence of the cyclic lactone-based ionic liquid and polymer monomer with the structure of formula I in the modified material helps to cooperate with the PVDF in the active material layer, and constructs a low-porosity, high-cycle solid-state electrode while further optimizing the bonding ability of PVDF; and when method 2 is used to prepare the low-porosity, high-cycle solid-state electrode, the cyclic lactone-based ionic liquid and polymer monomer with the structure of formula I can be used as a solvent to achieve the dispersion of the solute, and can also replace / cooperate with PVDF to play the role of an adhesive. In particular, when method 2 is used to prepare the positive electrode electrode, the cyclic lactone-based ionic liquid and polymer monomer with the structure of formula I can effectively fix the positive electrode active material and the conductive agent, thereby replacing PVDF and improving the heat dissipation and ion conductivity of the electrode.
[0137] As a further solution, method 2 is a preferred synthesis method.
[0138] As a further solution, the thermal initiation condition is curing in a vacuum environment at 70-90° C. for 10-14 hours.
[0139] As a further solution, the solvent is not limited in principle, and technicians can select the corresponding solvent according to their needs.
[0140] As a further solution, the method for synthesizing the first type of monomer comprises the following steps:
[0141] S4.1: In a first solvent, heating a first reactant having a structural formula of XRM and an ionic liquid to reflux, cooling, washing, and distilling under reduced pressure to obtain a cyclic lactone-based ionic liquid, wherein X is an oxygen heterocyclic group and M is a halogen;
[0142] The ratio of the first reactant to the ionic liquid is 1:1.05-2, preferably 1:1.1-1.5.
[0143] S4.2: In a second solvent, stir and wash the cyclic lactone-based ionic liquid and the alkali metal salt to obtain the electrolyte additive.
[0144] The mass ratio of the cyclic lactone-based ionic liquid to the alkali metal salt is 1:1.05-2, preferably 1:1.1-1.5.
[0145] As a further solution, the first solvent in step S4.1 is ethyl acetate.
[0146] As a further solution, the ionic liquid in step S4.1 is selected from one of imidazoles, pyridines, quaternary ammoniums, quaternary phosphoniums, pyrrolidines, piperidines, and functionalized ionic liquids.
[0147] As some preferred schemes, the ionic liquid is selected from the group consisting of N-methylimidazole, triethylamine, 4-methylpyridine, 1-methylpyrrolidine, N-methylpiperidine, and N,N-diethylmethylamine.
[0148] As a further scheme, the temperature of heating reflux in step S4.1 is 60-90°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, and the reflux time is 24-72h, for example, 24h, 28h, 32h, 36h, 40h, 44h, 48h, 52h, 56h, 60h, 64h, 68h, 72h. In the reaction of step S4.1, the higher the temperature of heating reflux and the longer the time, the higher the yield of cyclic lactone-based ionic liquid, but it is also accompanied by more side reactions. When a reflux temperature of 60-90°C and a reflux time of 24-72h are selected, the occurrence of side reactions can be reduced while effectively ensuring a higher yield.
[0149] As a further solution, in step S4.2, the second solvent is deionized water.
[0150] As a further solution, in step S4.2, the alkali metal salt is selected from one or more of halide ions, phosphate ions, perchlorate ions, sulfonimide ions, oxalate borate ions, sulfonate ions, and acetate ions.
[0151] As a further scheme, in step S4.2, the stirring time is 2 to 24 hours, for example, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours.
[0152] On the third aspect, the present solution also provides a battery that uses a low-porosity, high-cycle solid-state electrode as the electrode.
[0153] In a fourth aspect, the present solution further provides an energy storage device, comprising the battery. The energy storage device refers to a modular device composed of a plurality of batteries, and is used to store and release electrical energy.
[0154] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0155] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0156] Example 1
[0157] Cyclic lactone-based ionic liquid I-3 Preparation
[0158] First, 20 g of hydroxymethyldioxolane (CAS No.: 931-40-8), 18 g of chloroacetic acid, and 50 g of chloroform were added to a reactor and refluxed at 85° C. and stirred for 5 h. After the stirring was completed, the mixture was cooled to room temperature, and then distilled under reduced pressure. The mixture was washed three times with 50 mL of deionized water, and then distilled under reduced pressure to obtain a halogenated cyclic lactone.
[0159] Take 20g of halogenated cyclic lactone, 30g of triethylamine and 40g of ethyl acetate and add them into a reactor, reflux and stir at 85℃ for 24h, cool to room temperature after stirring, wash three times with 40mL of ethyl acetate, and obtain a cyclic lactone-based ionic liquid after reduced pressure distillation;
[0160] Subsequently, 20 g of the lactone-based ionic liquid and 20 g of LiTFSI were dissolved in 30 mL of deionized water, stirred at room temperature for 2 h, and then washed three times with 50 mL of deionized water to obtain the lactone-based ionic liquid I-3.
[0161] Positive electrode preparation:
[0162] Take 2.4g of cyclic lactone-based ionic liquid I-3, 0.6g of diethylene glycol diacrylate, 0.15g of Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) and 0.3 g of lithium bis(trifluoromethylsulfonyl)imide were mixed to obtain a first solution;
[0163] 0.012g aluminum fluoride, 0.003g azobisisobutyronitrile, 6.5g LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), 0.5g conductive carbon black (Super P) is added to the first solution and evenly dispersed to obtain a second solution that can be used as a positive electrode slurry. The positive electrode slurry is evenly coated on the surface of the aluminum foil with a coating thickness of 200μm. It is vacuum heated at 80℃ for 12h to solidify the cyclic lactone-based ionic liquid monomer and polymer monomer in the electrode to obtain a low-porosity and high-cycle solid-state electrode.
[0164] Preparation of batteries
[0165] A 25μm thick PP separator was used, and a 0.6mm thick lithium metal was used as the negative electrode. An electrolyte (1mol / L LiPF6EC:DMC:EMC=1:1:1) was added. In this electrolyte formula, EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) were mixed in a volume ratio of 1:1:1 to assemble NCM-lithium metal button batteries.
[0166] Example 2
[0167] The synthesis method and preparation steps are the same as those of Example 1, except that the amount of the lactone-based ionic liquid I-3 added is 2.1 g.
[0168] Example 3
[0169] The synthesis method and preparation steps are the same as those in Example 1, except that 0.3 g of diethylene glycol diacrylate is added.
[0170] Example 4
[0171] The synthesis method and preparation steps are the same as in Example 1, using 0.15 g of Li 10 GeP2S 12 (LGPS) replaces LATP.
[0172] Example 5
[0173] Cyclic lactone-based ionic liquid I-1 Preparation
[0174] First, 20 g of 4-(chloromethyl)-1,3-dioxolane-2-one (CAS No.: 2463-45-8), 15 g of N-methylimidazole, and 20 g of ethyl acetate were added to a reactor and refluxed at 85° C. and stirred for 24 h. After stirring, the mixture was cooled to room temperature, washed three times with 30 mL of ethyl acetate, and distilled under reduced pressure to obtain a cyclic lactone-based ionic liquid. Subsequently, 20 g of the cyclic lactone-based ionic liquid obtained in step (1) and 20 g of LiTFSI were dissolved in 30 mL of deionized water. After stirring at room temperature for 2 h, the mixture was washed three times with 50 mL of deionized water to obtain an ion-exchanged cyclic lactone-based ionic liquid, i.e., the electrolyte additive.
[0175] The method and steps for preparing the positive electrode plate are the same as those in Example 1, except that the cyclic lactone-based ionic liquid I-1 is used to replace the cyclic lactone-based ionic liquid I-3.
[0176] Example 6
[0177] Cyclic lactone-based ionic liquid I-6 Preparation
[0178] First, 20 g of 1,2-oxaphospholane-4-methanol-2-methoxy-2-oxide (CAS No.: 633278-49-6), 18 g of bromopropionic acid, and 50 g of chloroform were added to a reactor and refluxed at 85° C. for 5 h. After stirring, the mixture was cooled to room temperature, and distilled under reduced pressure. The mixture was washed three times with 50 mL of deionized water, and distilled under reduced pressure to obtain a halogenated cyclic lactone.
[0179] Subsequently, 20 g of halogenated cyclic lactone, 30 g of N-methylpiperidine, and 40 g of ethyl acetate were added to a reactor and refluxed at 85° C. and stirred for 24 h. After the stirring was completed, the mixture was cooled to room temperature, washed three times with 40 mL of ethyl acetate, and distilled under reduced pressure to obtain a cyclic lactone-based ionic liquid.
[0180] Finally, 20 g of the cyclic lactone-based ionic liquid obtained in step (1) and 20 g of LiClO4 were dissolved in 30 mL of deionized water, stirred at room temperature for 2 h, and then washed three times with 50 mL of deionized water to obtain the electrolyte additive.
[0181] The method and steps for preparing the positive electrode plate are the same as those in Example 1, except that the cyclic lactone-based ionic liquid I-6 is used to replace the cyclic lactone-based ionic liquid I-3.
[0182] Comparative Example 1
[0183] 0.3 g PVDF and 2.7 g NMP were mixed and evenly dispersed to obtain positive electrode slurry, which was evenly coated on the surface of aluminum foil and heated at 80° C. in vacuum for 12 h to obtain a pole piece.
[0184] A 25μm thick PP separator was used, and a 0.6mm thick lithium metal was used as the negative electrode. An electrolyte (1mol / L LiPF6EC:DMC:EMC=1:1:1) was added. In this electrolyte formula, EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) were mixed in a volume ratio of 1:1:1 to assemble NCM-lithium metal button batteries.
[0185] Comparative Example 2
[0186] The synthesis method and preparation steps are the same as those in Example 1, except that diethylene glycol diacrylate is not added.
[0187] Comparative Example 3
[0188] The synthesis method and preparation steps are the same as those of Example 1, except that the lactone-based ionic liquid I-3 is not added.
[0189] Comparative Example 4
[0190] The synthesis method and preparation steps are the same as those in Example 1, except that LATP is not added.
[0191] Comparative Example 5
[0192] The synthesis method and preparation steps are the same as those of Example 1, except that vinyl imidazole bis(trifluoromethanesulfonyl)imide salt is used to replace the cyclic lactone-based ionic liquid I-3.
[0193] Comparative Example 6
[0194] The synthesis method and preparation steps are the same as those of Example 1, except that an amine-containing piperidine-based bistrifluoromethanesulfonyl imide salt is used to replace the cyclic lactone-based ionic liquid I-3.
[0195] The specific parameters of Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.
[0196] Performance Testing
[0197] Cyclic performance test
[0198] The battery was tested for long cycle charge and discharge at 0.5C. The voltage range was 2.5-4.3V.
[0199] Peel force test
[0200] The positive electrode sheet was cut into 400m*15mm size using a FHSD-LX30 universal electronic tensile testing machine, and a 180°C peeling test was performed.
[0201] First coulombic efficiency = (first discharge capacity / first charge capacity) * 100%
[0202] Secondary discharge capacity = first discharge capacity / mass of active sulfur
[0203] 200 cycle capacity retention rate = (200th discharge capacity / first discharge capacity) * 100%
[0204] The test results are shown in Table 2.
[0205] Table 1
[0206]
[0207]
[0208] Table 2
[0209]
[0210] Compared with Comparative Examples 1-6, Examples 1-6 exhibit lower porosity, and while ensuring the porosity, exhibit better first-efficiency and first-cycle discharge specific capacity, as well as better cycle capacity retention rate, indicating that the addition of polymerizable composite electrolyte can effectively reduce the electrode porosity, while optimizing the first-efficiency and first-cycle discharge specific capacity, thereby improving the battery cycle performance.
[0211] From Example 1 and Comparative Example 1, it can be observed that when no polymerizable composite electrolyte is added, the surface loading and porosity of Comparative Example 1 are significantly worse than those of Example 1. At the same time, its electrochemical performance and cycle capacity are both weaker than those of Example 1, which once again illustrates that the addition of modified materials can effectively reduce the porosity of the electrode and optimize the electrochemical performance.
[0212] From Example 1 and Comparative Examples 2-4, it can be observed that if you want to fully increase the surface load, reduce the porosity, and optimize the electrochemical performance, cyclic lactone-based ionic liquids, polymer monomers, and inorganic ceramic electrolyte nanoparticles are all essential. This may be because it is necessary to give full play to the coordination of the three in order to optimize the electrochemical ability of the pole piece while ensuring the low porosity of the pole piece. In the uncured slurry stage, the cyclic lactone-based ionic liquid having a structure of formula I and the polymer monomer having at least one reactive active group can be used as a solvent to evenly disperse the active substance and the conductive agent, avoiding the hole problem caused by the volatilization of traditional solvents, thereby obtaining a dense, low-porosity electrode and increasing the surface load. During the curing process, the solute and the ionic liquid are fixed in the cross-linked network, replacing the traditional PVDF, enhancing the heat dissipation capacity of the battery, and constructing a lithium ion transmission channel, improving the ion conductivity. In addition, the introduction of inorganic ceramic electrolyte nanoparticles helps to adjust the cross-linking density, construct an ion transmission channel, improve the conductivity and ion migration number, and adsorb impurities to improve safety performance. Finally, the cyclic lactone-based ionic liquid undergoes ring-opening polymerization during the cycle to form a solid electrolyte membrane, enhance ionic conductivity, and inhibit side reactions. Taking all these factors into consideration, the polymerizable composite electrolyte of the present invention effectively reduces the porosity of the electrode, optimizes the electrochemical performance, and improves the cycle performance of the battery.
[0213] In Example 1 and Comparative Examples 5-6, it can be observed that when conventional ionic liquids are used to replace the cyclic lactone-based ionic liquids having the structure of Formula I proposed in this scheme, the various performances of Comparative Examples 5-6 are lower than those of Example 1. This may be because the ionic liquids used in Comparative Examples 5-6 have a poor coordination effect with the polymer monomer having at least one reactive active group and the inorganic ceramic electrolyte nanoparticles, and it is difficult to fully exert the complex effect of the three. Therefore, the overall performance of Comparative Examples 5-6 is lower than that of Example 1.
[0214] It can be observed from Examples 1-2 that Example 1 exhibits better first effect and cycle capacity retention than Example 2. This may be because compared with Example 2, the content of the cyclic lactone-based ionic liquid I-3 in Example 1 can form a more stable CEI film, thereby optimizing the performance of Example 1; and it can also be observed in Examples 1 and 3 that compared with Example 3, Example 1 also has stronger adhesion ability. This may be because the diethylene glycol diacrylate in Example 1 can cooperate with the cyclic lactone-based ionic liquid I-3 to construct a more uniformly cross-linked three-dimensional network structure, thereby enhancing the adhesion ability.
[0215] The effects of inorganic solid electrolytes on their performance are discussed in Examples 1 and 4. It can be observed that, based on similar surface loadings, Example 1 has better electrochemical capabilities than Example 4. This may be because, compared to LGPS, when inorganic ceramic electrolyte nanoparticles are used, it helps to further coordinate the cyclic lactone-based ionic liquid I-3 with diethylene glycol diacrylate to construct a better ion transport channel, thereby optimizing the electrochemical performance of Example 1.
[0216] It can be observed in Examples 1, 5, and 6 that Examples 1 and 5 exhibit stronger peeling force and better first efficiency, first-cycle discharge specific capacity, and cycle capacity retention rate than Example 6. Although the porosity in Example 6 is slightly better than that in Examples 1 and 5, the overall performance of Examples 1 and 5 is still better than that of Example 6. This may be because the ionic liquid cationic groups selected from quaternary ammonium and imidazole in Examples 1 and 5 can, on the one hand, combine with polymer monomers to disperse solutes, thereby constructing a more uniform and stable cross-linked network, thereby improving the bonding ability and ion conductivity of Examples 1 and 5. On the other hand, the presence of quaternary ammonium and imidazole ionic liquid cationic groups may also be able to construct a more stable CEI film during the recycling process, thereby protecting the active material particles during the circulation process, thereby improving the cycle performance of Examples 1 and 5.
[0217] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A low-porosity, high-cycle solid-state electrode, characterized in that: It includes a current collector and an active material layer disposed on the current collector and containing a modified material: wherein, The synthetic monomers of the modified material include a first type of monomer and a second type of monomer; the first type of monomer includes a cyclic lactone-based ionic liquid having a structure of Formula I, the second type of monomer includes a polymer monomer having at least one reactive active group, the polymer monomer has a carbon-carbon unsaturated bond, and the electrode also includes electrolyte nanoparticles; The cyclic lactone-based ionic liquid having the structure of formula I is Wherein, X is an oxygen heterocyclic group, Y + is an ionic liquid cationic group; R is one of a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, a substituted or unsubstituted alkyl ester group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted cycloalkyl group, and when substituted, the substituent is selected from halogen; Z - One or more selected from the group consisting of halogen ions, phosphate ions, perchlorate ions, sulfonimide ions, oxalate borate ions, sulfonate ions, and acetate ions; The reactive active group is selected from any one of vinyl, allyl, epoxypropyl, amine and hydroxyl groups or a combination of two or more thereof.
2. The low-porosity, high-cycle solid-state electrode according to claim 1, characterized in that: The oxygen heterocyclic group is selected from one of a cyclic carbonate group, a cyclic sulfate group, a sultone group, a cyclic phosphonate group, and a carboxylate group; The ionic liquid cationic group is selected from one of the functionalized ionic liquid cationic groups of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrolidine and piperidine; the R is selected from one of C1-C8 substituted or unsubstituted alkyl groups, C1-C8 substituted or unsubstituted alkoxy groups, C1-C8 substituted or unsubstituted alkyl ester groups, C2-C8 substituted or unsubstituted unsaturated hydrocarbon groups, C3-C8 substituted or unsubstituted cyclic hydrocarbon groups, and when substituted, the substituent is selected from halogen; The polymer monomer is selected from chain polymer monomers having unsaturated carbon-carbon bonds at the ends; Preferably, the oxygen heterocyclic group is selected from a cyclic carbonate group, the ionic liquid cationic group is selected from one of quaternary ammonium and imidazole ionic liquid cationic groups, and the R is selected from a C1-C6 substituted or unsubstituted alkyl ester group, and when substituted, the substituent is selected from a halogen; Preferably, the chain polymer monomer having an unsaturated carbon-carbon bond at the terminal is selected from chain polymer monomers having unsaturated carbon-carbon bonds at both ends.
3. The low-porosity, high-cycle solid-state electrode according to claim 1, characterized in that: The cyclic lactone-based ionic liquid having the structure of formula I is selected from Any one or more of them.
4. The low-porosity, high-cycle solid-state electrode according to claim 1, characterized in that: The electrolyte nanoparticles have a particle size of less than 500 nm; The material of the electrolyte nanoparticles is selected from any one or more of inorganic ceramic electrolytes, inorganic salt electrolytes, phosphate electrolytes, and sulfate electrolytes; Preferably, the material of the electrolyte nanoparticles is selected from inorganic ceramic electrolytes.
5. The low-porosity, high-cycle solid-state electrode according to claim 1, characterized in that: The polymerizable composite electrolyte also includes a lithium salt; The lithium salt is selected from lithium salts having a decomposition temperature higher than 80°C; The active material layer also includes an initiator; The initiator is selected from at least one of peroxides, azo compounds and persulfates; The mass ratio of the cyclic lactone-based ionic liquid having the structure of formula I, the polymer monomer, the electrolyte nanoparticles, and the lithium salt in the polymerizable composite electrolyte is selected from the range of (50-95): (0.1-40): (0.1-20): (5-20); Preferably, the mass proportion of the cyclic lactone-based ionic liquid having the structure of formula I in the polymerizable composite electrolyte is selected from 55 to 85 wt %; Preferably, the mass proportion of the polymer monomer having at least one reactive active group in the polymerizable composite electrolyte is selected from 10 to 30 wt %; Preferably, the total mass ratio of the initiator to the cyclic lactone-based ionic liquid and the polymer monomer is (0.5-5):100; Preferably, the mass proportion of the polymerizable composite electrolyte in the coating slurry is 10 to 35 wt %.
6. The low-porosity, high-cycle solid-state electrode according to claim 1, characterized in that: The coating slurry of the low-porosity high-cycle solid-state electrode also includes active material particles and conductive additives; The conductive additive accounts for 3 to 15 wt% of the coating slurry; Preferably, the mass proportion of the active material particles in the coating slurry is 60-85wt%; The low-porosity, high-cycle solid-state electrode also includes a current collector; The porosity of the low-porosity high-cycle solid-state electrode is 0.5-10%; The low-porosity high-cycle solid-state electrode is selected from any one of a positive electrode and a negative electrode; Preferably, the low-porosity, high-cycle solid-state electrode is a positive electrode.
7. A method for synthesizing the low-porosity, high-cycle solid-state electrode according to claim 1, characterized in that: The steps include: S1.1: Mix the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt in a stoichiometric ratio to obtain a first solution; S1.2: According to the stoichiometric ratio, the initiator is added to the first solution and mixed evenly to obtain the second solution, followed by coating, and then curing to obtain a low-porosity, high-cycle solid-state electrode; Among them, the active material and the conductive agent are introduced into the low-porosity high-cycle solid-state electrode by one of the following two methods: Method 1: The active material and the conductive agent are arranged in the active material layer on the surface of the current collector, and the second solution prepared in step S1.2 is applied to the surface of the active material layer, and then solidified to obtain a low-porosity, high-cycle solid-state electrode; Method 2: The active material and the conductive agent are added to the second solution in step S1.2, and then coated on the surface of the current collector, and then cured to obtain a low-porosity, high-cycle solid-state electrode.
8. The synthesis method according to claim 7, characterized in that The specific steps of method 1 are: S2.1: Adding the active material and the conductive agent to the solvent according to the stoichiometric ratio, mixing them evenly and coating them on the surface of the current collector to obtain a current collector provided with an active material layer; S2.2: Mixing the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt uniformly according to the stoichiometric ratio to obtain a first solution; S2.3: According to the stoichiometric ratio, the initiator is added to the first solution and mixed evenly to obtain a second solution, and the second solution is coated on the surface of the active material layer on the current collector, and after thermal curing, a low-porosity high-cycle solid-state electrode is obtained; The specific steps of method 2 are: S3.1: Mixing the first monomer, the second monomer, the electrolyte nanoparticles, and the lithium salt uniformly according to the stoichiometric ratio to obtain a first solution; S3.2: adding an initiator, an active material and a conductive agent to the first solution according to a stoichiometric ratio to obtain a second solution, coating the second solution on the surface of the current collector, and obtaining a low-porosity, high-cycle solid-state electrode after thermal curing; The heat curing condition is 70-90° C. in a vacuum environment and the curing time is 10-14 hours.
9. The synthesis method according to claim 7, characterized in that: The first type of monomer is synthesized by the following steps: S4.1: In a first solvent, a first reactant having a structural formula of XRM and an ionic liquid are heated to reflux, cooled, washed, and distilled under reduced pressure to obtain a cyclic lactone-based ionic liquid, wherein X is an oxygen heterocyclic group and M is a halogen; The ratio of the first reactant to the ionic liquid is 1:1.05-2, preferably 1:1.1-1.5; S4.2: In a second solvent, stirring and washing the cyclic lactone-based ionic liquid and the alkali metal salt to obtain the electrolyte additive; The mass ratio of the cyclic lactone-based ionic liquid to the alkali metal salt is 1:1.05 to 2, preferably 1:1.1 to 1.5; Preferably, the first solvent in step S4.1 is ethyl acetate; Preferably, the ionic liquid in step S4.1 is selected from one of imidazoles, pyridines, quaternary ammoniums, quaternary phosphoniums, pyrrolidines, piperidines, and functionalized ionic liquids; Preferably, the ionic liquid is selected from the group consisting of N-methylimidazole, triethylamine, 4-methylpyridine, 1-methylpyrrolidine, N-methylpiperidine, and N,N-diethylmethylamine; Preferably, the heating reflux temperature in step S4.1 is 60-90° C.; Preferably, in step S4.2, the second solvent is deionized water; Preferably, in step S4.2, the alkali metal salt is selected from one or more of halide ions, phosphate ions, perchlorate ions, sulfonimide ions, oxalate borate ions, sulfonate ions, and acetate ions; Preferably, in step S4.2, the stirring time is 2 to 24 hours.
10. A battery or energy storage device, characterized in that: A low-porosity, high-cycle solid-state electrode comprising the low-porosity, high-cycle solid-state electrode as described in any one of claims 1-6 or a low-porosity, high-cycle solid-state electrode synthesized by the synthesis method as described in any one of claims 7-9.
Citation Information
Patent Citations
Inorganic coordination polymers as gelling agents
CN106463764A
Solid electrode and preparation method and application thereof
CN114335556A
Modified ionic liquids containing bicyclic phosphate moieties
CN115668422A
Lithium ion battery
CN118572189A
Electrolyte composition
JP2004162019A